Improving Knowledge on Pathways to Functional Outcome in Schizophrenia: Main Results From the Italian Network for Research on Psychoses - Giuliani, Luigi; Giordano, Giulia Maria; Bucci, Paola; Pezzella, Pasquale; Brando, Francesco; Galderisi, Silvana (Frontiers in Psychiatry, 2021)
The identification of factors associated to functional outcome of subjects with schizophrenia is a great challenge of current research oriented to the personalization of care. The Italian Network for Research on Pychoses is a network of 26 university psychiatric clinics and/or mental health departments aimed to carry out multicenter research projects to improve the standards of prevention, diagnosis and treatments of schizophrenia. The Network has promoted two main studies, a cross-sectional and a longitudinal one, and seven “add-on” studies. The cross-sectional study of the Network included 921 subjects with schizophrenia, 379 unaffected first-degree relatives of these patients and 780 healthy controls. Results from this study documented that social and non-social cognition, functional capacity, negative symptoms, resilience, and family or social incentives strongly influence a measure of global functioning. The follow-up study included 618 patients from the original sample and has produced evidence of the key role of cognition, functional capacity, the experiential domain of negative symptoms and everyday life skills in predicting functional outcome. The longitudinal study demonstrated that social cognition and the experiential domain of negative symptoms had an impact on interpersonal functioning, while non-social cognition on everyday life skills. Both non-social cognition and social cognition predicted work skills. The research question concerning the relationships of cognitive impairment and negative symptoms has been investigated with an innovative approach, using a structural equation model (SEM) and a network analysis. Both analyses demonstrated that only the Experiential domain of negative symptoms had a distinct direct effect on functioning. The network analysis showed that Expressive deficit was connected to functional capacity, as were social and non-social cognitive variables, and to disorganization. These findings were confirmed by the follow-up study.. The add-on studies showed distinct electrophysiological correlates of the two negative symptom domains and the partial overlap between disorganization and neurocognitive impairment. Morover, they identified and characterized a specific subgroup of patients suffering from schizophrenia with autism-spectrum symptoms. The NIRP studies have implications for personalized management of patients with schizophrenia and highlight the need for a careful assessment of several domains rarely evaluated in clinical settings.